Reliability of total haemocyte count as stress indicator in giant tiger shrimp (Penaeus monodon) - Lew, Hong Chuan; Mohamed Din, Mohamed Shariff (2010)
Stress is the main factor causing losses to the aquaculture industry including shrimp farming. It depresses the immunity of shrimp, increasing susceptability to disease and thus causing high mortality and morbidity. Stress in shrimp basically come from the management and farming activity such as transportation, handling, ablation of eye stalk for reproduction, anesthesia for mild to painful procedure and other practice. Previous reports have shown the reduction of total hemocyte count (THC) when shrimp was challenged with stress. In the present study, THC of giant tiger shrimp (Penaeus monodon) were compared between control group and 3 treatments i.e., subjected to unilateral eyestalk ablation, post 10% ethanol anesthesia stress and transport stress respectively. Statistical analysis showed that there was significant (P<0.01) difference for THC between control group and those with unilateral eyestalk ablation. Significant mean difference (P<0.01) was also seen in control group and those with post-anesthesia stress using 10% ethanol. However, there was no significant mean difference between control group and those subjected to transport stress.